Understanding Islamic ethics and its significance on character building - Abdul Rahim, Adibah (2013)
The most critical challenge facing Muslim today is the lack of the spiritual ethical dimension of life, and one of the most powerful means to overcome this problem is the adherence to the code of ethics. This paper attempts at clarifying the concept of Islamic ethics as a basic pillar for a healthy society. It explains about the need of ethics for the development of individual and society by highlighting its definitions, and its significance on the character building. The author tries to present ethics as the counter part of other sciences, such as, law, politics, science, economics, and others for such sciences become soulless or insignificant if detached from ethics. The paper concludes that Muslim character should develop along with Islamic ethics and its application into daily affairs of Muslims’ lives should be given its due attention